2021
DOI: 10.1158/0008-5472.can-20-1541
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous and Endogenous Sources of Serine Contribute to Colon Cancer Metabolism, Growth, and Resistance to 5-Fluorouracil

Abstract: Serine is a non-essential amino acid generated by the sequential actions of phosphoglycerate dehydrogenase (PHGDH), phosphoserine aminotransferase (PSAT1), and phosphoserine phosphatase (PSPH). Increased serine biosynthesis occurs in several cancers and supports tumor

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…In colorectal cancer cells, overexpression of PSAT1 induces enhanced tumorigenic properties compared to control cells in a xenograft mouse model and confers resistance to oxaliplatin treatment [ 79 ]. Similarly, both depletion of PSAT1 in colorectal cancer cells and removal of serine from mouse diet inhibit tumor growth and increase the antitumor efficacy of 5-FU in vivo [ 80 ]. Consistently, in esophageal squamous cell carcinoma (ESCC) tissues, expression of PSAT1 is increased compared to adjacent non-cancer tissues and is significantly associated with disease stage [ 81 ].…”
Section: Serinementioning
confidence: 99%
“…In colorectal cancer cells, overexpression of PSAT1 induces enhanced tumorigenic properties compared to control cells in a xenograft mouse model and confers resistance to oxaliplatin treatment [ 79 ]. Similarly, both depletion of PSAT1 in colorectal cancer cells and removal of serine from mouse diet inhibit tumor growth and increase the antitumor efficacy of 5-FU in vivo [ 80 ]. Consistently, in esophageal squamous cell carcinoma (ESCC) tissues, expression of PSAT1 is increased compared to adjacent non-cancer tissues and is significantly associated with disease stage [ 81 ].…”
Section: Serinementioning
confidence: 99%
“…Previous studies have demonstrated that several genetic features of tumors influence the response to serine starvation ( DeNicola et al, 2015 ; Kottakis et al, 2016 ; LeBoeuf et al, 2020 ; Maddocks et al, 2013 , 2017 ). In addition, the ability to synthesize serine de novo can allow cancer cells to proliferate when exogenous serine is limiting ( Diehl et al, 2019 ; Montrose et al, 2021 ; Méndez-Lucas et al, 2020 ; Ngo et al, 2020 ; Sullivan et al, 2019b ; Tajan et al, 2021 ). We examined whether the ability of basal breast cancer cells to proliferate without exogenous S/G is reliant on serine biosynthesis by treating basal HCC1806 cells with the PHGDH inhibitor PH-755 while growing with and without S/G.…”
Section: Resultsmentioning
confidence: 99%
“…This and other work motivated the development of PHGDH inhibitors as potential cancer treatments ( Mullarky et al, 2016 ; Pacold et al, 2016 ; Rohde et al, 2018 ; Wang et al, 2017 ). While the inhibition of serine synthesis has shown efficacy in some models and is still being evaluated, it is becoming clear that in some circumstances it is not effective because of extracellular serine that can be taken up to offset the inhibition of de novo biosynthesis ( Chen et al, 2013 ; Montrose et al, 2021 ; Méndez-Lucas et al, 2020 ; Ngo et al, 2020 ; Nilsson et al, 2012 ; Sullivan et al, 2019b ; Tajan et al, 2021 ). Because our goal was to identify cases in which lineage-dependent gene expression reduces pathway redundancy, we examined whether the very low expression of PSAT1 found in luminal tumors limits their ability to synthesize serine and creates a dependence on exogenous serine for growth.…”
Section: Introductionmentioning
confidence: 99%
“…Serine metabolism has been reported to contribute to CRC metabolism and growth 34 and enzymes involved in serine synthesis such as phosphoglycerate dehydrogenase (PHGDH) 35 are found in higher levels in colonic tumor tissue than paired normal tissue 36 . These studies did not consider sex differences which might lend to a potential sex-specific phenomenon.…”
Section: Discussionmentioning
confidence: 99%